Mathematics
50382193345038105717
21

5. -4n + 7 + 2n =1 A.1 B.3 C.-3 D.4 6.4(y - 4) = 8 A.-2 B. 2 C. 4 D. 6

+2
(2) Answers
ufnwish73

5. -4n+ 7+ 2n= 1 ⇒ (-4n+ 2n)+ 7= 1 (combine like terms) ⇒ -2n= 1-7 ⇒ -2n= -6 ⇒ n= -6/(-2) ⇒ n= 3 Final answer: B. 3~ 6. 4(y-4)= 8 ⇒ y-4= 8/4 ⇒ y-4= 2 ⇒ y= 2+4 ⇒ y= 6 Final answer: D. 6~

TDAWG2171

If you would like to solve the equation -4 * n + 7 + 2 * n = 1, you can do this using the following steps: -4 * n + 7 + 2 * n = 1 -2 * n = 1 - 7 -2 * n = -6        /(-2) n = -6 / (-2) n = 3 The correct result would be B. 3. If you would like to solve the equation 4 * (y - 4) = 8, you can do this using the following steps: 4 * (y - 4) = 8 4 * y - 4 * 4 = 8 4 * y = 8 + 16 4 * y = 24      /4 y = 24 / 4 y = 6 The correct result would be D. 6.

Add answer